Digital Marketing Campaign Training Using Artificial Intelligence for MSMEs in the UMKM Naik Kelas Program of Karawang Regency - Santoso, Adi; Sulaiman, Eman; Vigory Gloriman Manalu (Society : Jurnal Pengabdian Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia's economic development; however, many MSME actors still face challenges in implementing effective digital marketing strategies. The rapid advancement of Artificial Intelligence (AI) has created new opportunities for MSMEs to improve marketing efficiency, customer engagement, and content personalization. This community service activity aimed to enhance the knowledge and practical skills of MSME participants in utilizing AI technologies for digital marketing campaigns. The activity was conducted as part of a training and mentoring program within the “UMKM Naik Kelas Kabupaten Karawang” initiative on July 4, 2026, and involved MSME owners from various business sectors. The implementation methods included lectures, demonstrations, case studies, and hands-on practice using AI-based tools for content creation, campaign optimization, customer communication, and market analysis. The results demonstrated an improvement in participants' understanding of AI-based digital marketing strategies, as reflected in interactive discussions, practical exercises, and participant engagement during the training sessions. Participants showed increased awareness of AI applications for content creation, advertising optimization, and customer communication.